Transparency and Accountability Mechanisms in Ghana's Petroleum Revenue Management Act: A Critical Analysis and Socio-Political Contextualisation with Counterpoints from Norway and Botswana - Adomako-Kwakye, Chris (Department of Private Law, 2022)
Once known as the Gold Coast due to minerals, Ghana has very little to show for that. The revenue generated from minerals in Ghana went into the Consolidated Fund associated with mismanagement and corruption. Auditor-General's annual reports support this assertion, and the Commission of Inquiry set up to investigate the source of the wealth of politicians, and public officials confirmed mismanagement of State resources. Ghana enacted the Petroleum Revenue Management Act (PRMA) upon discovering oil and separated the oil revenue from the Consolidated Fund. The PRMA guides the management of oil revenue to benefit all Ghanaians and cause growth. Despite the PRMA, Ghanaians are pessimistic about the management of the oil revenue due to mismanagement issues. It includes the Finance Minister's discretionary power, capping the Ghana Stabilisation Fund, transferring the Annual Budget Funding Amount into the Consolidated Fund, oil revenue spent in ways not provided for by the Act, institutional weakness, and lack of national development plans. The thesis seeks to determine how the enactment of the PRMA would help deal with mismanagement through a socio-political analysis of the Act. It does so by discussing the PRMA of Ghana critically, taking into account lessons from Botswana and Norway on a series of subquestions: a) the discretionary powers of decision-makers and its effect on the management of oil revenue, b) features of quality institutions that aid the management of resource revenue, c) how various types of funds and their utilisation assist the management of oil revenue d) the role of policy planning and project reporting dealing with non-compliance. The thesis deliberates these issues, focusing solely on the PRMA and its mechanisms to achieve transparency and accountability. It considered the reports issued by the Auditor-General and the Public Interest Accountability Committee (PIAC) on the utilisation of created funds and the lack of institutional autonomy. The thesis shows that although the PRMA has its strengths, flaws remain and these surface, especially in implementing the law. The design of the PRMA creates a discrepancy between its objectives and its operation requiring legislative reform. Looking at these weaknesses more closely, the thesis argues for a paradigm shift to precede recommended legislative reform to assuage the fears of Ghanaians by offering recommendations for improving the PRMA to optimise the oil revenue.